Vitamin C, From Supplement to Treatment: A Re-Emerging Adjunct for Cancer Immunotherapy? - Kouakanou, Léonce; Peters, Christian; Brown, Christine E.; Kabelitz, Dieter; Wang, Leo D. (Frontiers in Immunology, 2021)
Vitamin C (VitC), in addition to its role as a general antioxidant, has long been considered to possess direct anti-cancer activity at high doses. VitC acts through oxidant and epigenetic mechanisms, which at high doses can exert direct killing of tumor cells in vitro and delay tumor growth in vivo. Recently, it has also been shown that pharmacologic-dose VitC can contribute to control of tumors by modulating the immune system, and studies have been done interrogating the role of physiologic-dose VitC on novel adoptive cellular therapies (ACTs). In this review, we discuss the effects of VitC on anti-tumor immune cells, as well as the mechanisms underlying those effects. We address important unanswered questions concerning both VitC and ACTs, and outline challenges and opportunities facing the use of VitC in the clinical setting as an adjunct to immune-based anti-cancer therapies.